2015
DOI: 10.4172/2155-6180.1000223
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis of Premature Infants Admitted to Neonatal Int ensive Care Unit (NICU) in Northwest Ethiopia using Semi-Parametric Fr ailty Model

Abstract: This study presents an extension of Cox model to frailty model in which the Cox-proportional of baseline hazard and the gamma distribution is used as frailty distribution. The gamma distribution is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 21 publications
3
16
0
Order By: Relevance
“…All studies were published from 2012 to 2019. Six of the studies identified employed hospital-based cohort designs [24][25][26][27][28][29]; the remaining four applied cross-sectional designs [30,31] ( Table 1).…”
Section: Description Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…All studies were published from 2012 to 2019. Six of the studies identified employed hospital-based cohort designs [24][25][26][27][28][29]; the remaining four applied cross-sectional designs [30,31] ( Table 1).…”
Section: Description Of Studiesmentioning
confidence: 99%
“…The capacity of NICU in terms of bed-size and staffing varied from hospital to hospital. It ranged from16-beds NICU [32] to 50-beds NICU [26] and some hospitals had comprehensive neonatal care that included intensive care, KMC, and isolation rooms [30,24,27,28,26]. It was staffed with medical interns, pediatric residents, physicians, and nurses.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations